Structural mechanisms of inflammasome assembly. (21st November 2014) - Lu, Alvin; Wu, Hao
<x xml:space="preserve">Abstract</x> Inflammasomes are supramolecular signaling complexes that activate a subset of caspases known as the inflammatory caspases, an example of which is caspase 1. Upon stimulation by microbial and damage‐associated signals, inflammasomes assemble to elicit the first line of host defense via the proteolytic maturation of cytokines interleukin‐1β and interleukin‐18, and by induction of pyroptotic cell death. Inflammasome assembly requires activation of an upstream sensor, a downstream effector and, in most cases, an adaptor molecule such as apoptosis‐associate speck‐like protein containing a caspase recruitment domain (ASC). Depending on whether ASC is required, inflammasomes can be categorized into ASC‐dependent and ASC‐independent inflammasomes. Here, we review current understandings of the structures of inflammasomes, as probed using traditional structural methods, as well as biochemical, biophysical and single‐molecule methods. The key structural scaffold for inflammasome assembly is composed of filaments of Pyrin domains and caspase recruitment domains (CARD) in the sensor, adaptor and effector components. Nucleated polymerization appears to govern the ordered assembly process from activation of a Pyrin domain‐containing sensor such as AIM2 by dsDNA or NLRP3 by extracellular particulates, to recruitment of the Pyrin domain and CARD‐containing adaptor ASC, and finally to activation of CARD‐containing caspase 1. The underlying filamentous architecture of inflammasomes and the cooperativity in the assembly may explain the 'all‐or‐none' response in inflammasome activation. Inflammasomes are tightly regulated by a number of cytosolic inhibitors, which may change the morphology and assembly kinetics of inflammasomes. Biochemical and cellular studies suggest that Pyrin domain and CARD filaments possess prion‐like properties in propagating inflammasome activation within and between cells.